PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, KONSERVATISME, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Mayerson, Evan; Wijaya, Henryanto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to determine the effect of leverage, liquidity, profitability, conservatism, and firm size on earnings quality in family manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The total sample used is 37 family manufacturing companies. Data processing using computer-based program Eviews version 12. This study uses multiple linear regression analysis. The results of this study indicate that leverage has no effect on earnings quality. Liquidity has a positive and significant effect on earnings quality. Profitability has no effect on earnings quality. Conservatism has a positive and significant effect on earnings quality. Firm size has no effect on earnings quality. The implication in this study is that companies that have liquid assets in order to cover short-term debts owned by the company and the company must be conservative so that companies are more careful in recognizing profits and expenses in the company. To build trust between agents and shareholders.